(untitled) (Italian Review of Legal History, 2020)
The issue concerning reparation of war damages and the connected responsibility of the State towards their occurrence represented a particularly debated topic in Italy since the achieving of national Unity. The identification of refundable damages, the choice between reparation and indemnity, the distinction between “war actions” and “preparatory activities”, are only some of several problematic perspectives about reparation of war damages. With the First World War, reparation of war damages returned to being an absolutely current topic, being matched with the idea of “social solidarity”, until to the theorizing of reparation of war damages as a legal obligation of the State towards the damaged citizen. The difficulties concerning the configuration and the features of the reparation of war damages – in particular about the legal meaning of words like “indemnity” and “reparation” and their correct application – characterized also the work of the Royal Commission for Postwar that was established with decree of 21 March 1918, n. 361.